Temporal relationship of serum markers and tissue damage during acute intestinal ischemia/reperfusion - Guzmán de la Garza, Francisco Javier; Ibarra Hernández, J. M.; Cordero Pérez, Paula; Villegas Quintero, P.; Villarreal Ovalle, C. I.; Torres González, Liliana; Oliva Sosa, N. E.; Alarcón Galván, Gabriela; Fernández Garza, Nancy Esthela; Muñoz Espinosa, Linda Elsa; Camara Lemarroy, Carlos Rodrigo; Carrillo Arriaga, José Gerardo (2013)
OBJECTIVE: It is essential to identify a serological marker of injury in order to study the pathophysiology of intestinal ischemia reperfusion. In this work, we studied the evolution of several serological markers after intestinal ischemia reperfusion injury in rats. The markers of non-specific cell damage were aspartate aminotransferase, alanine aminotransaminase, and lactic dehydrogenase, the markers of inflammation were tumor necrosis factor alpha, interleukin-6, and interleukin-1 beta, and the markers of intestinal mucosal damage were intestinal fatty acid binding protein and D-lactate. We used Chius classification to grade the histopathological damage. METHODS: We studied 35 Wistar rats divided into groups according to reperfusion time. The superior mesenteric artery was clamped for 30 minutes, and blood and biopsies were collected at 1, 3, 6, 12, 24, and 48 hours after reperfusion. We plotted the mean ¡ standard deviation and compared the baseline and maximum values for each marker using Student’s t-test. RESULTS: The maximum values of interleukin-1 beta and lactic dehydrogenase were present before the maximal histopathological damage. The maximum tumor necrosis factor alpha and D-lactate expressions coincided with histopathological damage. Alanine aminotransaminase and aspartate aminotransferase had a maximum expression level that increased following the histopathological damage. The maximum expressions of interluken-6 and intestinal fatty acid binding protein were not significantly different from the Sham treated group. CONCLUSION: For the evaluation of injury secondary to acute intestinal ischemia reperfusion with a 30 minute ischemia period, we recommend performing histopathological grading, quantification of D-lactate, which is synthesized by intestinal bacteria and is considered an indicator of mucosal injury, and quantification of tumor necrosis factor alpha as indicators of acute inflammation three hours after reperfusion.